Geographical Factors and Their Impact on the Cultivation of Field Crops in Misan Governorate - Rami Eidan, Sahar ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
Natural and human geographical factors represent some of the most important aspects affecting the cultivation of agricultural crops, including field crops. The production and quality of any agricultural crop are determined by the nature of the surface, the prevailing climate and its various elements, soil characteristics, and water resources, in addition to human factors that play a significant role in agricultural expansion, improving both the quantity and quality of production, and providing suitable conditions for cultivation. The interaction of these factors clearly contributes to determining the spatial variation of field crop cultivation among different regions, and their availability constitutes the foundation of agricultural success. Maysan Governorate is one of the southern governorates of Iraq known for its agricultural production. It is distinguished by the cultivation of various agricultural crops of economic importance and possesses geographical potentials that contribute to the development of the agricultural sector if properly utilized, particularly with regard to its suitable climate and diverse soils. The study revealed that the soils along the banks of the Tigris River are the most suitable for cultivation due to their ease of drainage. It was also found that the waters of the Tigris River play an essential role in irrigating agricultural lands, in addition to the importance of labor force in carrying out agricultural operations. Accordingly, the research examines the geographical factors in Maysan Governorate and identifies their impact on the cultivation of field crops. The study focuses on wheat, barley, Shlab (rice) , and maize, with special attention given to the effect of these factors on the variation in cultivated areas and production among the administrative units, which consist of six districts and nine sub-districts within the study area. The research also seeks to identify the necessary strategies for developing and improving agricultural production efficiency. DOI: https://doi.org/10.54633/2333-025-058-024